Rendition of Planting and Payoff in Localized Films: A Case Study - Elahe Ebtehaji; Mahboubeh Moghadas; Milad Mehdizadkhani (Media and Intercultural Communication: A Multidisciplinary Journal)
Planting and payoff or foreshadowing is a narrative technique in screen writing where a future event is foreshadowed by clues and hints. These clues may seem meaningless at first, however, their importance is revealed as the story unfolds in the payoff scene. This study aimed to investigate the rendition of planting and payoff in the Persian amateur subtitling and official dubbing of ten Anglophone narrative movies. Multimodal transcription and Chaume’s signifying codes were used to describe scenes containing plantings and their corresponding payoffs. Then, translation strategies adopted by the translators of each mode were identified. Finally, concluding remarks on the success of each mode in rendering foreshadowing were suggested. Findings demonstrated the dubbed and subtitled versions were equally successful in rendering the planting and payoffs. However, the reasons for the failure in each mode were different. Finally, it was suggested that careful attention to signifying codes, and particularly based on the results of this study to iconographic and graphic codes, should be paid while rendering planting and payoff.